Strengthening the sweetpotato community of practice - Low, Jan W.; McEwan, M. (International Potato Center, 2015)
The flyer captures the achievements made from June 2014 to July 2015 to establish a growing and vibrant sweetpotato community of practice that enables sweetpotato researchers, development agents, farmers and consumers to obtain and apply sweetpotato knowledge effectively. The flyer details the development of the Community of Practice for SpeedBreeders and Sweetpotato Support Platforms; and the establishment of three new CoPs: Seed Systems and Crop Management; Marketing, Processing, and Utilization, and Monitoring, Learning and Evaluation.